Bridges in Luck - Past and Present - Nosaliuk, Nataliia; Andreychuk, Alexander (Budownictwo i Architektura / Civil and Architectural Engineering, 2014)
This article is about bridges that existed in the past and currently used by residents and guests in Lutsk. Here are shown the rich history of bridges in Lutsk, and the importance of the existence of these structures in city. The main waterway is the river Stir now. About the river Glushets is resembled only a street with the same name. The article is a reviewed of archival documents, sometimes very modest, is used as a backdrop for modern bridges in Lutsk.